Update on mycotoxin contamination of maize and peanuts in East African Community Countries - Edgar Mugizi Ankwasa; Imade Francis; Tanvir Ahmad (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2021)
The East African Community (EAC) is a regional Inter-Governmental body comprising of Uganda, Kenya, Tanzania, Rwanda, Burundi, and South Sudan. This region produces and extensively consumes maize and peanuts as staple foods. Maize and peanuts are susceptible to fungal growth and mycotoxin contamination and this is favored by high temperatures, high humidity as well as other factors such as grain damage by birds or insects, poor postharvest handling, and storage. Mycotoxins are toxic secondary metabolites of fungi that contaminate food with far-reaching consequences on human and animal health in addition to causing huge economic losses. Major mycotoxins of concern in maize and peanuts are Aflatoxins, Fumonisins, Zearalenone, and Deoxynivalenol. Among the East African Community countries aflatoxins and fumonisins are the most detected and researched mycotoxins in maize and peanuts. The highest reported aflatoxin contamination levels in maize and peanuts among the East African Community countries were 48,000μg/kg and 7,525μg/kg respectively both of which were recorded in products from Kenya while the highest fumonisin contamination in maize was 18,184 μg/kg which was reported in products from Tanzania. Human beings are exposed to mycotoxins mainly through the consumption of contaminated foods or their products. The East African Community through the East African Bureau of Standards set regulatory limits for aflatoxins and fumonisins in maize and peanuts at 5 ppb for aflatoxin B1, 10 ppb for total aflatoxins, and 2000 ppb for fumonisins. This paper reviews the current literature on mycotoxin contamination of Maize and Peanuts in the East African Community region, current regulations, their negative consequences on health and trade as well as factors contributing to their high prevalence in the region.